MAIN PROBLEMS OF ADAPTATION OF YOUNG WORKERS IN UKRAINE UNDER CURRENT CONDITIONS - SKLIARUK, Tetiana; TERLETSKA, Anastasiia (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article examines the main problems of adaptation of young workers in Ukraine under current conditions, which are characterized by labour market instability, digitalization of work processes, migration mobility, and the consequences of the full-scale war. The relevance of the topic is determined by the fact that effective adaptation of young people at the initial stages of employment is a crucial prerequisite for the formation of sustainable career trajectories, reduction of staff turnover, and improvement of the efficiency of human capital utilization both at the organizational level and within the national economy.The purpose of the article is to analyse the problems of adaptation of young workers in the contemporary labour market of Ukraine and to identify the key factors influencing the effectiveness of their professional and socio-psychological adaptation. The study employs general scientific and specialized research methods, including analysis and synthesis, systemic and structural-functional approaches, comparative analysis, as well as generalization of statistical and analytical data from international and national organizations. The article уточнено the essence of personnel adaptation and substantiates its significance for young workers as a process of integration into the organizational environment, mastering professional responsibilities, and developing effective communication within work teams. The main approaches to personnel adaptation (professional, socio-psychological, organizational, and psychophysiological) are analysed, and the role of digital tools in enhancing the effectiveness of adaptation programmes is identified. Particular attention is paid to the characteristics of the youth labour market in Ukraine. It is established that young workers represent one of the most vulnerable groups due to high unemployment rates, a significant share of NEET youth, the widespread use of informal employment, and the mismatch between educational training and employers’ requirements. Based on official statistics and analytical reports, it is shown that these factors lead to a prolonged transition from education to employment, employment instability, and increased risks of social vulnerability. The impact of the full-scale war on the adaptation of young workers is also examined, particularly through mass migration, job losses, increased competition in local labour markets, and the intensification of the “brain drain” phenomenon. It is substantiated that the war has significantly complicated the professional adaptation of young people and intensified macroeconomic consequences in the form of human capital losses and declining economic activity.The article demonstrates that adaptation difficulties faced by young workers are complex in nature and require a systemic approach to their resolution. The practical significance of the study lies in the possibility of applying the findings in the development of adaptation and mentoring programmes within organizations, improvement of state youth employment policies, expansion of dual education, and promotion of lifelong professional learning programmes.Prospects for further research include assessing the effectiveness of modern adaptation tools for young workers, analysing sector-specific features of adaptation processes, and examining the role of digital HR solutions and public institutions in creating conditions for sustainable professional development of young people during Ukraine’s post-war recovery.
Keywords: young workers; personnel adaptation; youth labour market; youth unemployment; informal employment; professional adaptation; labour migration; human capital